Step by Step Implementation of DSRM for Personalization of Reading - Mansor, Marzita; Wan Adnan, Wan Adilah; Abdul Wahid, Rohaizah; Hamid, Jamilah (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
This paper aims to discuss step-by-step activities of the implementation of Design Science Research Methodology (DSRM) in the development of Personalization teaching and learning materials for children. DSRM is adapted in the development of personalized teaching and learning materials due to its potential to provide specific guidelines based on specific outcomes. This paper revealed the potential of DSRM as a reliable and comprehensive methodology that leads the developer on step by step processes to perform the development. Apart from that this study provides details description on the development of personalized teaching and learning materials that is successfully developed using the DSRM methodology as guidelines.